DISHARMONISASI KEPALA DAERAH (ANALISIS FRAMING ROBERT N. ENTMAN PADA PEMBERITAAN MEDIA ONLINE ULASAN.CO) - Ella Afnira; Eki Darmawan; Ryan Anggria Pratama (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2024)
This research aims to understand and analyze how the online media outlet Ulasan.co frames the news about the leadership of the Governor and Deputy Governor of the Riau Islands, where three months after their inauguration, they were hit by issues of disharmony. Ulasan.co is the most prominent online media platform in the Riau Islands that frequently highlights these issues. This study analyzes the news texts from Ulasan.co titled "Dirty Plates" Amid the Ansar-Marlin Dispute. The research findings indicate that Ulasan.co's news framing is considered to lack "covering both sides" as it tends to present statements from only one party. The analysis is conducted using Robert N. Entman's framing model, yielding the following results: Problem Identification (identifying the problem's causes) is attributed to internal political conflict; Diagnose Causes (assessing the root causes) point to the Deputy Governor; Make Moral Judgements (moral evaluation) involve the professional stance of the Governor in maintaining governance continuity; and Treatment Recommendations (problem-solving and resolution) involve the call for resolving the issues and conflicts between the Governor and Deputy Governor, thereby allowing them to collaborate once again in advancing the Riau Islands Province.